Bioequivalence of three florfenicol preparations in broilers (Journal of Advanced Veterinary and Animal Research, 2014)
This study was aimed to determine the bioequivalence of three different preparations of florfenicol using non-drugged broiler chickens. A total of 28 broiler chickens aging 30-day were divided into four equal groups; these were Group I, II, III, and IV. The birds of Group I (for effective substance) were given intravenous (i.v.) administration of florfenicol dosed at 40 mg/kg body weight (b.wt.). The birds of Group II (for reference drug), Group III (for test-1 drug), and Group IV (for test-2 drug) received florfenicol preparations with water (dosed at 40 mg/kg b.wt.) through intracrop administration. Blood samples were collected periodically from the birds of all four groups, and blood plasma was separated. Levels of florfenicol and its metabolite (florfenicol amine) in the plasma were measured by High Performance Liquid Chromatography (HPLC). In this study, the limit of detection (LOD) for florfenicol and florfenicol amine were recorded as 0.017 and 0.78 ?g/mL, respectively. On the other hand, the recovery of florfenicol and florfenicol amine were 83.4-84.6 and 82.2-83.8%, respectively. Based on the values of area under the curve (AUC), maximum concentration (Cmax), and time to maximum concentration (Tmax), test-1 drug was found to be acceptable, whereas test-2 drug was remained below the acceptable limits (80-125%) of AUC and Cmax. Thus, it was concluded that test-1 drug was bioequivalent as compared to the reference drug.   http://dx.doi.org/10.5455/javar.2014.a28